2019
DOI: 10.1037/dhe0000074
|View full text |Cite
|
Sign up to set email alerts
|

Transgender graduate students’ experiences in higher education: A mixed-methods exploratory study.

Abstract: Little research has explored the experiences of transgender or gender-nonconforming (TGNC) students in higher education. Further, only 1 study has included the perspectives of TGNC graduate students (McKinney, 2005), and the experiences of students who identify with nonbinary gender identities (e.g., genderqueer, agender) are scarce in the literature (Nicolazzo, 2016a(Nicolazzo, , 2016b. This study aims to address these gaps. Ninety-one graduate students completed an online survey aimed at understanding the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 46 publications
(114 reference statements)
3
70
2
Order By: Relevance
“…On the other hand, a 2011 survey 11 of 28 US colleges of veterinary medicine revealed that > 20% of LGBTQ+ students heard homophobic comments occasionally to very frequently at school. This study did not evaluate effects on mental health or academic outcomes; however, findings from other studies [29][30][31][32] suggest that exposure to harassment and discrimination hinders the academic performance of LGBTQ+ students.…”
mentioning
confidence: 91%
“…On the other hand, a 2011 survey 11 of 28 US colleges of veterinary medicine revealed that > 20% of LGBTQ+ students heard homophobic comments occasionally to very frequently at school. This study did not evaluate effects on mental health or academic outcomes; however, findings from other studies [29][30][31][32] suggest that exposure to harassment and discrimination hinders the academic performance of LGBTQ+ students.…”
mentioning
confidence: 91%
“…Second, our sample did not have a large enough number of transgender and nonbinary students (n = 13) to analyze as a separate gender group; thus, in order to include these students in our analysis, we opted to combine their responses with cisgender females, another gender group that has been historically marginalized in the academy. However, we do note that the academic experiences of transgender and nonbinary students greatly differ from cisgender females (Goldberg et al, 2019) and future research should aim to recruit larger samples to accurately capture each group's unique lived experiences. Finally, although our qualitative analyses provide further insights into graduate student experiences during the pandemic, our openended questions were rather limited in their content.…”
Section: Limitationsmentioning
confidence: 86%
“…A study of LGBTQ undergraduate students found that trans students have the most negative perceptions of campus climate, classroom climate, and curriculum inclusivity, probably because they experience more harassment than their cisgender queer peers (Garvey and Rankin 2015). Goldberg, Kuvalanka and dickey (2019) discovered that transgender and nonbinary graduate students experience frequent and sometimes deliberate misgendering that takes a mental and emotional toll, especially when it comes from faculty members who proclaim to be allies or mentors who must be relied on for career success. Catalano (2015) learned that transmasculine and nonbinary students are subject to additional pressures on campus, such as pressure to appear stereotypically masculine, when that may not be their goal.…”
Section: Employment Issues Among Trans Populationsmentioning
confidence: 99%
“…Catalano (2015) learned that transmasculine and nonbinary students are subject to additional pressures on campus, such as pressure to appear stereotypically masculine, when that may not be their goal. Many trans graduate students conclude that efforts to correct faculty or to educate them about trans identities are simply not worth it and they choose to preserve their emotional energy in order to survive graduate school, rather than defend their identities (Goldberg, Kuvalanka and dickey 2019). Tierney (1993) wrote in reference to LGBQ scholars that hiding parts of themselves requires enormous energy that detracts from their work and this invisibility only reinforces prejudice.…”
Section: Employment Issues Among Trans Populationsmentioning
confidence: 99%